Adaptation and Preliminary Psychometric Evaluation of the Indonesian Academic Anxiety Scale for Boarding School High School Students - Moh Fuadudin; Nur Hidayah; Diniy Hidayatur Rahman; Azmawati Mohammed Nawi; Abi Fa’izzarahman Prabawa (Institut Agama Islam Negeri Kerinci, Indonesia, 2026)
Academic anxiety poses a critical challenge within school counseling frameworks due to its detrimental effects on cognitive focus, academic drive, performance outcomes, and overall psychological well-being. These vulnerabilities are often exacerbated in residential educational settings, where rigorous academic obligations intersect with boarding school responsibilities. To address the need for validated assessment tools in this context, this study adapted the Academic Anxiety Scale (AAS) into Indonesian and evaluated its psychometric integrity among Islamic senior high school students in boarding environments. A cross-sectional psychometric design was conducted with a sample of 342 students aged 15–19 years. The adaptation protocol encompassed forward-back translation, expert appraisal, cross-cultural adaptation, pilot readability testing, and content validity quantification via the Content Validity Index (CVI). Confirmatory Factor Analysis (CFA) was performed to test structural validity, while Cronbach’s Alpha and McDonald’s Omega evaluated internal consistency reliability. Expert review yielded robust content validity (S-CVI = 1.00), and CFA confirmed the instrument's original unidimensional structure with favorable goodness-of-fit parameters (CFI = .924, TLI = .905, IFI = .925, GFI = .977, RMSEA = .089, SRMR = .044). Internal reliability was exceptionally strong (Cronbach’s α = .894; McDonald’s ω = .898). These psychometric outcomes demonstrate that the Indonesian AAS is a valid, reliable, and culturally sound tool for measuring academic anxiety in boarding school populations, offering educational counselors and researchers a robust diagnostic instrument to support targeted mental health interventions.